2002
DOI: 10.1016/s0022-5347(05)64155-9
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Renal Tumor Destruction Using Radio Frequency Interstitial Ablation

Abstract: In our series radio frequency therapy did not result in total tumor destruction when specimens were examined with hematoxylin and eosin or NADH staining. We believe that radio frequency interstitial tumor ablation of renal cell carcinoma without subsequent tissue resection should continue to be an investigational treatment modality for those who would otherwise undergo partial or radical nephrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(56 citation statements)
references
References 18 publications
2
48
0
6
Order By: Relevance
“…Another important point about biopsy is that some researchers have discussed post-ablative biopsy to confirm the adequacy of a radiographic definition of ablative success [28,29]. However, most of these researchers have used hematoxylin and eosin staining to assess post-treatment biopsies, which is inadequate for assessing cellular viability, as the heat denaturation during ablation results in preservation of the cellular formation [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Another important point about biopsy is that some researchers have discussed post-ablative biopsy to confirm the adequacy of a radiographic definition of ablative success [28,29]. However, most of these researchers have used hematoxylin and eosin staining to assess post-treatment biopsies, which is inadequate for assessing cellular viability, as the heat denaturation during ablation results in preservation of the cellular formation [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Local efficacy of RFA is the most controversial topic: while some studies on lesions treated with RFA and then resected immediately or within a short period assert that necrosis induced by the treatment is often incomplete [29,30], others demonstrate that tissue destruction can be complete [31,32]. These differences can reflect the scarce standardization of the procedure, which is performed with different ablation systems and techniques (single or multiple-electrode arrays, cooled or hooked needles, dry or wet-tip probes; varying power and time settings; temperature-or impedance-based protocols) [15].…”
Section: Discussionmentioning
confidence: 99%
“…Michaels et al [25] from the Lahey Clinic also reported unfavorable outcomes related to RFA treatment. This group performed open RFA for 15 patients with a total of 20 tumors (mean, 2.4 cm in size) followed by partial nephrectomy.…”
Section: Clinical Resultsmentioning
confidence: 99%